The Effect of Indirect Feedback on Students' Recount Text Writing Ability at SMK Fatihul Ulum - Viky Maulana; Widya Oktarini; Yeni Mardiana Devanti (JELP Journal of English Language and Pedagogy, 2026)
Writing skill is one of english skill besides of listening, reading, and speaking. This skill is important to students in study english but some students face challenges when produce it, especially in past tense. This research aims to investigate the effect of indirect feedback on students’ writing ability in recount text. The method of research uses quantitative method using quasi-experimental as the design with sample of this research is students of SMK Fatihul Ulum grade X. The results show that indicates that indirect feedback can reduce the error of students’ recount text writing ability. In addition, this strategy also engages the critical thinking of students, self-correction, and makes efficient time of learning. It is recommended that integrating indirect feedback as part of the writing learning strategy to encourage students to be more active in the process of revision. It also suggests for future research to exploring the combination of several types of indirect feedback like underlining, circling, etc or combination of other types of feedback like direct feedback to see which approaches are more effective in certain aspects of writing.